Noise thermometry for ultralow temperatures - Fleischmann, Andreas; Reiser, Andreas; Enss, Christian (Journal of low temperature physics, 2020)
In recent years, current-sensing dc-SQUIDs have enabled the application of noise thermometry at ultralow temperatures. A major advantage of noise thermometry is the fact that no driving current is needed to operate the device and thus the heat dissipation within the thermometer can be reduced to a minimum. Such devices can be used either in primary or relative primary mode and cover typically several orders of magnitude in temperature extending into the low microkelvin regime. Here we will review recent advances of noise thermometry for ultralow temperatures.
Gesehen am 21.10.2021